2011
DOI: 10.1098/rspb.2011.1738
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Mendelian and clonal genome transmission in a sexually reproducing, all-triploid vertebrate

Abstract: Meiosis in triploids faces the seemingly insuperable difficulty of dividing an odd number of chromosome sets by two. Triploid vertebrates usually circumvent this problem through either asexuality or some forms of hybridogenesis, including meiotic hybridogenesis that involve a reproductive community of different ploidy levels and genome composition. Batura toads (Bufo baturae; 3n ¼ 33 chromosomes), however, present an all-triploid sexual reproduction. This hybrid species has two genome copies carrying a nucleol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 57 publications
1
62
0
Order By: Relevance
“…However, most of unisexual vertebrates, such as kleptogenetic Ambystoma salamanders (Bi and Bogart, 2010;Spolsky et al, 1992), hybridogenetic Poeciliopsis fish (Quattro et al, 1992), gynogenetic Amazon molly (Lampert and Schartl, 2008;Schartl et al, 1995), Phoxinus eosneogaeus hybrids (Angers and Schlosser, 2007), and gynogenetic Cobitis (Janko et al, 2003), have been revealed to have long history and large ranges of geographical distribution (Avise, 2008). And, high genetic diversity has been extensively observed in gynogenetic or hybridogenetic fish (Angers and Schlosser, 2007;Cunha et al, 2011;Schmidt et al, 2011;Stöck et al, 2012), kleptogenetic amphibians (Bi and Bogart, 2010) and parthenogenetic reptiles (Fujita et al, 2007;Kupriyanova, 2009). Significantly, these rare unisexual animals are largely associated with polyploidy origin (Neaves and Baumann, 2011;Otto et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of unisexual vertebrates, such as kleptogenetic Ambystoma salamanders (Bi and Bogart, 2010;Spolsky et al, 1992), hybridogenetic Poeciliopsis fish (Quattro et al, 1992), gynogenetic Amazon molly (Lampert and Schartl, 2008;Schartl et al, 1995), Phoxinus eosneogaeus hybrids (Angers and Schlosser, 2007), and gynogenetic Cobitis (Janko et al, 2003), have been revealed to have long history and large ranges of geographical distribution (Avise, 2008). And, high genetic diversity has been extensively observed in gynogenetic or hybridogenetic fish (Angers and Schlosser, 2007;Cunha et al, 2011;Schmidt et al, 2011;Stöck et al, 2012), kleptogenetic amphibians (Bi and Bogart, 2010) and parthenogenetic reptiles (Fujita et al, 2007;Kupriyanova, 2009). Significantly, these rare unisexual animals are largely associated with polyploidy origin (Neaves and Baumann, 2011;Otto et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, a lot of genetic knowledge including molecular basis of reproduction trait and numerous polymorphic DNA markers has been investigated and characterized from the triploid form (Gui and Zhou, 2010;Gui and Zhu, 2012). Similar to other polyploid salamanders, frogs and fish (Lampert and Schartl, 2010;Schlupp, 2005;Stöck et al, 2012), the triploid form can also reproduce by sperm-dependent gynogenesis, and many diverse gynogenetic clones have been discriminated by different genetic markers, such as transferrin Yang et al, 2001, RAPD and SCAR markers (Zhou et al, 2001(Zhou et al, , 2000b, microsatellite (Guo and Gui, 2008) and mtDNA sequence (Apalikova et al, 2008;Brykov et al, 2005;Li and Gui, 2008). Interestingly, a minor but significant portion (approx 1-10%) of triploid males were found in the triploid form, and normal sperm production and their sexual reproduction ability have been demonstrated by experimental propagation and genetic analysis in the triploid form (Gui and Zhou, 2010;Peng et al, 2009;Sun et al, 2010;Zhou et al, 2000a).…”
Section: Introductionmentioning
confidence: 99%
“…We also confirmed with nuclear markers that the maternal ancestor (B m ) of B. baturae was related to B. shaartusiensis. These new data represent the first nuclear and multilocus evidence for the maternal ancestry of B. baturae, which is one of the few gonochoristic all-triploid vertebrates (Stöck et al, 2012), for which previous hints on this hybrid species' maternal ancestor came only from mtDNA (Litvinchuk et al, 2011). The close relationship between B. baturae and B. shaartusiensis, that had been inferred from identical mtDNA sequences (Litvinchuk et al, 2011; Figure 1), contrasts with the deeper Stöck et al 2012) Bp1 Bp1 (= NOR+ in Stöck et al 2012) Bm Bp2 Bp2 (=NOR+ in Stöck et al 2012) Pm Pm (=TT in Stöck et al 2010) Pp Pp (=LL in Stöck et al 2010) …”
Section: Allopolyploid Origins and Genome Topologiesmentioning
confidence: 78%
“…The ancestor of the two paternal sets (B p B p ) also remains unidentified (Figure 1). Triploidy is maintained by differential male and female forms of meioses: in the male germ line, the B m set (referred to as NOR-in Stöck et al, 2012) is eliminated, followed by a diploid meiosis of the B p sets (referred to as NOR+ in Stöck et al, 2012) that only produces recombined haploid B p sperm, whereas in the female germ line, the B m set is first duplicated, followed by a tetraploid meiosis that produces diploid B m B p ovules (Stöck et al, 2012). Hence, the B p set is sexually transmitted by both sexes, whereas the B m set is only maternally and clonally transmitted, along with mtDNA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation